2019
DOI: 10.1039/c9cy02025j
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective reduction of quinoline over Rh–C60 nanocatalysts

Abstract: Highly selective hydrogenation of quinoline by electron-deficient Rh species containing fullerene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…For example, Wang et al reported the successful application of a catalyst based on Ru single atoms in the UiO-66 metal–organic framework (MOF) for the catalytic hydrogenation of quinolone . Recently, Luo et al used Rh nanoparticles supported on fullerene C 60 to achieve excellent activity and selectivity toward the synthesis of 1,2,3,4-tetrahydroquinoline (py-THQ) . However, catalysts supported on solids must be separated from the products after the reaction through filtration, centrifugation, or precipitation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al reported the successful application of a catalyst based on Ru single atoms in the UiO-66 metal–organic framework (MOF) for the catalytic hydrogenation of quinolone . Recently, Luo et al used Rh nanoparticles supported on fullerene C 60 to achieve excellent activity and selectivity toward the synthesis of 1,2,3,4-tetrahydroquinoline (py-THQ) . However, catalysts supported on solids must be separated from the products after the reaction through filtration, centrifugation, or precipitation .…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, Luo et al used Rh nanoparticles supported on fullerene C 60 to achieve excellent activity and selectivity toward the synthesis of 1,2,3,4tetrahydroquinoline (py-THQ). 17 However, catalysts supported on solids must be separated from the products after the reaction through filtration, centrifugation, or precipitation. 5 These T h i s c o n t e n t i s processes severely affect the reusability of catalysts due to a gradual and significant loss of the catalyst in each cycle.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Taking into consideration this previous result, we examine here the possibility of using Ru/PVP catalysts to directly transform furfural into 1,2-PeD. Knowing that this transformation is sensitive to support effects [9,14,15] and our experience of tuning activity and selectivity in catalysed reactions by changing the adsorbates on the metallic surfaces [30][31][32][33], we have studied the effect of the in situ addition of organic ligands in order to examine their impact in the outcome of this chemical transformation. The modulation of the catalytic properties of heterogeneous catalysts using surface adsorbates is an important field in catalysis, yet it is in its infancy [34].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hydrides of N-heteroarenes, which are obtained by the hydrogenation of aromatics, play an important role in the agrochemical and pharmaceutical industries. Recently, a heterogeneous catalysis system applied in such processes undergo rapid development. Notably, catalysts supported by noble metals, such as Ru, Rh, and Ir, provide a good catalytic platform and are successfully used in different aromatic hydrogenation reactions. However, most of the studies on these processes concentrate on a simple model reaction. , The molecules often have more intricate structures in practical industry applications. Consequently, rational design and synthesis of supported metal catalysts with superb mass enrichment combined with excellent active sites are of equal importance for the catalytic reactions in pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%